EFFECT OF PUBLIC SECTOR ACCOUNTING IMPLEMENTATION IN FRAUD PREVENTION - Arifah, Fitrian Puji; Setyawan, Supanji (Transpublika Publisher, 2022)
This study expects to find and portray the attributes of extortion that happen in the public area in the computerized time and foster models of use of Public Area Bookkeeping to forestall misrepresentation that happens in the public area in the advanced age. The exploration was a writing survey study obtained from articles as per the examination point for additional investigation. The outcomes showed that the attributes of extortion in the public area that happened in the advanced time incorporate the utilization of confusions with respect to the job of computerized innovation in the execution of public bookkeeping errands, the usage of advanced innovation to streamline open doors for misrepresentation, taking advantage of issues in human blunder and absence of information in the utilization of computerized innovation, utilizing advanced innovation items, to do misrepresentation. Utilization of Public Area Bookkeeping can forestall misrepresentation in the public area in the advanced period whenever executed by thinking about a few factors that impact extortion, like execution responsibility, and joined by the use of misrepresentation counteraction techniques which incorporate specialized methodologies, two worldview approaches, and preventive systems.